Factors affecting safe pesticide-use behaviors among farm plant agriculturists in northeastern Thailand - Bunliang Suphim; Archin Songthap (BMC, 2024)
Background Pesticide poisoning is a major public health problem in Thailand and is the result of intensive inappropriate and unsafe use of pesticides. This analytical cross-sectional study aimed to determine the factors affecting safe pesticide-use behaviors among farm plant agriculturists in northeastern Thailand. Methods The study sample included 427 farm plant agriculturists in Loei Province, northeastern Thailand. Individuals were randomly selected by a multistage random sampling technique. The following data were collected via a self-administered questionnaire consisting of 8 parts: (1) sociodemographic characteristics, (2) knowledge about pesticide use, (3) perceived severity of impact from pesticide use among farm plant agriculturists, (4) perceived susceptibility to pesticide use, (5) perceived self-efficacy in the modification of safe pesticide-use behaviors, (6) perceived outcome of the modification of safe pesticide-use behaviors, (7) social support, and (8) safe pesticide-use behaviors. Frequencies, percentages, means, standard deviations, and multiple regression analyses were employed for data analysis. Results The majority of participants (79.4%) had high scores for safe pesticide-use behaviors among farm plant agriculturists (scores of 112-150). Factors that significantly affected safe pesticide-use behaviors included knowledge about pesticide use (β = 0.282), social support (β = 0.217), reading information from pesticide labels before pesticide use (β = 0.207), perceived self-efficacy (β = 0.186), female sex (β = -0.140), rice farmer status (β = 0.129), corn farmer status (β = 0.127), perceived susceptibility (β = 0.126), having received information from the internet (β = -0.124), and perceived severity (β = -0.098). Together, these 10 factors were found to explain 32.5% of the safe pesticide-use behaviors among farm plant agriculturists. Conclusions Our findings indicate that there is a need to increase the number of promotional activities related to the safe use of pesticides through social support and training, with the aim of increasing the overall level of knowledge, perceived self-efficacy, perceived susceptibility, and modification of the perceived impact severity of pesticide use. Thus, relevant agencies should promote and support the safe use of pesticides by farm plant agriculturists. Summary This study revealed that the factors affecting safe pesticide-use behaviors among farm plant agriculturists included knowledge about pesticide use, social support, reading pesticide container labels, perceived self-efficacy in the modification of pesticide-use behaviors, sex, rice farmer status, corn farmer status, perceived susceptibility to pesticide use, having received information from the internet, and perceived severity of impact from pesticide use.